Delivering Long‐term Surgical Care in Underserved Communities: The Enabling Role of International NPOs as Partners. Issue 6 (16th April 2017) - Kohnke, Emily J.; Mukherjee, Ujjal Kumar; Sinha, Kingshuk K.
Abstract : The efforts of not‐for‐profit organizations (NPOs) toward enabling health care delivery in underserved communities across the globe are well‐acknowledged. To date, little is known about the workings and sustenance of NPO‐enabled long‐term health care delivery in underserved communities, and even less about NPO‐enabled surgical care delivery. Further, health care delivery in underserved communities is a context that is often characterized by primitive and poor record keeping, data scarcity and poor data quality. Therefore, conducting research on health care delivery in such contexts is particularly challenging. The central question motivating this study is: How can international NPOs enable the long‐term delivery of surgical care in underserved communities? To overcome the data challenges, we use multi‐method triangulation as the research design to conduct this study. Specifically, we adopt a grounded theory approach with small sample statistical analysis for empirical validation. We triangulate insights from qualitative and quantitative data analyses to develop and validate an integrative framework for an international NPO‐enabled long‐term surgical care delivery in underserved communities. The setting for this study is Children's HeartLink, an international medical non‐profit organization based in the United States, which partners with health care delivery organizations in developing countries to enable the diagnosis and treatment of children with congenital heart disease (CHD). The focus of this study is the Children HeartLink's partnership with the First Hospital of Lanzhou University (FHLU) located in the underserved and impoverished Gansu province of China. In Gansu province, the CHD incidence rate is six times China's average. The time‐period of this study is 11 years, 1998–2008. The key contribution of this study is the integrative framework for an international NPO‐enabled long‐term surgical care delivery in underserved communities. The framework demonstrates how an international NPO's efforts related to affordability, provider awareness, and physical access are interdependent, and how the efforts interact and impact the surgical care delivery outcome. Contrary to conventional wisdom, the framework provides new and nuanced insights such as the following: (i) an international NPO's efforts related to affordability (e.g., funding) or provider awareness (e.g., knowledge transfer) alone has limited direct impact on long‐term surgical care outcome; (ii) instead of having a direct impact on the volume of surgeries, an international NPO's effort related to affordability moderates (positively interacts with) the positive association between its efforts related to provider awareness and physical access to surgical care delivery infrastructure, thus impacting the volume of surgeries; and (iii) an international NPO's efforts related to provider awareness and physical access are complementary for long‐term surgical care delivery – i.e., the effort related to provider awareness moderates by way of strengthening the positive association between the effort related to physical access and the volume of surgeries. Limitations of the study – e.g., small sample size for empirical validation of the grounded theory research findings and issues of generalizability – are acknowledged, and the directions of future research to address the limitations are discussed.